Deregulating and liberalizing the North-American telecommunications market: Explaining the US-approach - Peter F. Cowhey; John E. Richards (Hamburg Institute of International Economics (HWWA), 2002)
This paper examines the substantial regulatory changes in North American telecommunications markets over the past decade. We argue that a combination of U.S. domestic politics and the logic of international strategic positioning produced substantial and far-reaching reform driven primarily by multilateral actions at the WTO and a set of unilateral U.S. initiatives (primarily benchmarks). Internationally, although NAFTA played an important role as a ,,building block“ for the WTO agreement, we argue the lack of market coverage and more far-reaching WTO agreement ultimately limited NAFTA's role in driving reform. The logic of U.S. domestic politics also played a central role by putting certain constraints on what the U.S. would accept in a telecommunications trade deal. Specifically, there was broad political support for a deal, but the particular problems facing U.S. carriers in competitive international markets meant any deal had to cover all major telecommunications markets and had to address the very real anti-competitive opportunities open to foreign monopolists. Our argument suggests continued reform is likely to be driven primarily by the framework established at the WTO, although the U.S. will continue to use unilateral initiatives to drive reform acceptable to key U.S. political actors. – – Dieses Papier untersucht die erheblichen Regulierungsänderungen auf dem nordamerikanischen Telekommunikationsmarkt während der letzten Dekade. Wir argumentieren, dass die Kombination von amerikanischer Innenpolitik und internationalen strategischen Interessen bedeutende und weit reichende Reformen erzeugte, ausgelöst vor allem von multilateralen Aktivitäten in der WTO und einseitigen Initiativen der USA (insbesondere Benchmarks). Die NAFTA war zwar ein wichtiger ?Baustein? für das WTO-Abkommen, ihr begrenzter Wirkungsbereich und die weiter gehenden WTO-Vereinbarungen beeinträchtigten aber letztlich ihre Rolle als Triebkraft für Reformen. Die amerikanische Innenpolitik spielte einen zentralen Part, da sich hieraus Grenzen bezüglich der Inhalte eines Telekommunikationsabkommens ableiteten, das die USA zu akzeptieren bereit waren. Zwar gab es eine breite politische Unterstützung für ein Abkommen. Angesichts der spezifischen Probleme der amerikanischen Anbieter im internationalen Wettbewerb musste aber jede Vereinbarung alle großen Telekommunikationsmärkte umfassen, und sie musste den sehr konkreten Möglichkeiten ausländischer Monopolanbieter zur Beschränkung des Wettbewerbs Rechnung tragen. Unsere Überlegungen führen zu dem Ergebnis, dass weitere Reformen im Wesentlichen im Rahmen der WTO vorangetrieben werden dürften. Allerdings werden die USA auch in Zukunft einseitig Initiativen ergreifen, um Reformen durchzusetzen, die für ihre politischen Hauptakteure akzeptabel sind.
Keywords: F02; F13; L96; 330; International Economic Order; NAFTA; Trade Negotiations; Telecommunications; Telekommunikationspolitik; Deregulierung; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; WTO-Regeln; Vereinigte Staaten; NAFTA-Staaten